Fully closed-loop insulin delivery in inpatients receiving nutritional support: a two-centre, open-label, randomised controlled trial. Issue 5 (May 2019) - Boughton, Charlotte K; Bally, Lia; Martignoni, Franco; Hartnell, Sara; Herzig, David; Vogt, Andreas; Wertli, Maria M; Wilinska, Malgorzata E; Evans, Mark L; Coll, Anthony P; Stettler, Christoph; Hovorka, Roman
Summary: Background: Glucose management is challenging in patients who require nutritional support in hospital. We aimed to assess whether fully closed-loop insulin delivery would improve glycaemic control compared with conventional subcutaneous insulin therapy in inpatients receiving enteral or parenteral nutrition or both. Methods: We did a two-centre (UK and Switzerland), open-label, randomised controlled trial in adult inpatients receiving enteral or parenteral nutrition (or both) who required subcutaneous insulin therapy. Patients recruited from non-critical care surgical and medical wards were randomly assigned (1:1) using a computer-generated minimisation schedule (stratified by type of nutritional support [parenteral nutrition on or off] and pre-study total daily insulin dose [<50 or ≥50 units]) to receive fully closed-loop insulin delivery with faster-acting insulin aspart (closed-loop group) or conventional subcutaneous insulin therapy (control group) given in accordance with local clinical practice. Continuous glucose monitoring in the control group was masked to patients, ward staff, and investigators. Patients were followed up for a maximum of 15 days or until hospital discharge. The primary endpoint was the proportion of time that sensor glucose concentration was in target range (5·6–10·0 mmol/L), assessed in the intention-to-treat population. This trial is registered with ClinicalTrials.gov, number NCT01774565 . Findings: Between Feb 8, 2018, and Sept 21, 2018, 90 patients were assessed for eligibility, of whom 43 were enrolled and randomly assigned to the closed-loop group (n=21) or the control group (n=22). The proportion of time that sensor glucose was in the target range was 68·4% [SD 15·5] in the closed-loop group and 36·4% [26·6] in the control group (difference 32·0 percentage points [95% CI 18·5–45·5; p<0·0001]). One serious adverse event occurred in each group (one cardiac arrest in the control group and one episode of acute respiratory failure in the closed-loop group), both of which were unrelated to study interventions. There were no adverse events related to study interventions in either group. No episodes of severe hypoglycaemia or hyperglycaemia with ketonaemia occurred in either study group. Interpretation: Closed-loop insulin delivery is an effective treatment option to improve glycaemic control in patients receiving nutritional support in hospital. Funding: Diabetes UK, Swiss National Science Foundation, National Institute for Health Research Cambridge Biomedical Research Centre, Wellcome Trust, and European Foundation for the Study of Diabetes.